Sommo italiano. - Conti, Fulvio, author.
1 online resource (viii, 222 pages)
Keywords: "This book shows how Dante Alighieri has been represented in the Italian collective imagination from the late eighteenth century to the present day. Often held to be a precursor of Italian unity, the author of The Divine Comedy has been put forward both as a standard-bearer of a secular, anticlerical Italy and the embodiment of the concept of a deeply religious and Catholic nation; while he was later adopted by nationalist and fascists as well as a pop icon in the age of the internet and globalization. The book describes this long and fascinating history from a completely original point of view: the centuries-old myth of Dante is analysed from the perspective of cultural history. The sources employed include Dante commemorations, festivals and monuments, pilgrimages to his tomb, films and other media productions about Dante, as well as comic strips, advertisements and other cultural items dedicated to him"--